The Gender Wage Gap in Fisheries Labour Market: The Analysis of Sociodemographic and Work-Related Factors in Indonesia - Yulinda Nurul Aini (Pusat Studi gender dan Anak (PSGA) Universitas Islam Negeri Walisongo Semarang, 2022)
Income inequality is a challenge in the workplace, particularly in the fisheries subsector. Women are exploited, undervalued, and have limited educational opportunities. Age, education, employment position, duration of employÂment, and hours worked all contribute to this discrepancy. This study investigates how sociodemographic and work-related factors affect the gender wage gap in Indonesiaâ€™s fisheries subsector. 7.574 samples from the 2019 National Labour Force Survey were utilized. In this investigation, multiple linear regression analysis was employed. We find that age (p0.001), working hours (p0.001), and years worked (p0.001) have a positive and significant association with earnings. In all categories, women earn less than men on average. The discrepancy in income depending on age, hours worked, and years worked ranges between 350 and 600 thousand rupiahs. The interaction of education and job status is likewise significant (p0.02). This interaction also demonstrates the correlation between education level and the wealth gap. Inequality in income ranges from 450 to 800 thousand rupiahs for formal workers with a low level of education to a bachelor's degree, and from 450 to 550 thousand rupiahs for informal workers. For this reason, increasing education and empowering women are important factors in reducing income inequality and realizing the SDGs target to achieve decent work. Furthermore, government programs and policies at both the community and national levels need to adopt the norms, roles, and involvement of women in the fisheries subsector.